Spuriously raised serum amylase in a five-year-old girl: a note of caution in paediatric blood sampling. Issue 4 (November 2019) - Cull, Frith; Cullis, Paul S; Bradnock, Timothy J; Sabharwal, Atul J
Introduction: Capillary (finger prick) blood sampling is commonplace in paediatric practice but this method is prone to produce spurious laboratory results. Case presentation: A five-year-old girl presented with abdominal pain, epigastric tenderness, tachycardia and reduced oxygen saturation. A venous blood sample haemolysed, and serum amylase on a finger prick sample was reported as 2831 units/L. The working diagnosis was acute pancreatitis and respiratory tract infection. A repeat amylase 9 h later was within the normal range. The patient was known to bite her fingers and the possibility of salivary contamination was considered. Serum isoenzyme analysis confirmed presence of high salivary amylase levels with no pancreatic amylase detected. A viral respiratory tract infection and buried gastrostomy bumper were eventually thought to account for the patient's presentation. Conclusion: Increased awareness of the potential for salivary contamination of serum amylase in finger prick samples may prevent misdiagnoses of pancreatitis.